(untitled) (Journal of Scientific Research, 2017)
7-Hydroxy-3’,4’-methylenedioxy- and 7-benzyloxy-3’,4’-methylenedioxy flavanones have been synthesized starting from 2,4-dihydroxyacetophenone. Subsequently biocidal activities of the flavanones have been investigated along with their corresponding chalcones against some bacterial and fungal strains. 2’-Hydroxy-4’-benzyloxy-3,4-methylenedioxy chalcone (5) and its corresponding flavanone (7) showed good antibacterial and antifungal activities against some selected bacterial and fungal strains. On the other hand, 2’,4’-dihydroxy-3,4-methylenedioxy chalcone (4) showed no antibacterial and antifungal activities while its corresponding flavanone (6) showed a little antibacterial activity only at higher concentration but did not show antifungal activity. The synthesized chalcones and flavanones have been characterized using UV-Vis, IR and 1H NMRspectral data together with elemental analysis.